Biased attentional shifts associated with unilateral left neglect. - Shalev, L; Humphreys, G (2000)
Data are reported on the ability of a patient with unilateral left neglect to detect the presence of a gap in broken lines. Although there were some deficits in her left field in baseline conditions, more striking was the asymmetry in the effects of attentional cueing. Ipsilesional cues facilitated detection at far right locations most strongly. Contralesional cues facilitated detection at near left locations, but particularly when cues appeared on the far left. The results are interpreted in terms of biases in the lateral shifting of attention, with attention tending to overshoot to the right and undershoot to the left. The effects arise even when attentional engagement rather than disengagement is stressed.